Banco de dados geoespaciais: padronização e avaliação como suporte à Inteligência Territorial - Silvio Braz de Sousa; Daniel Carlos Alves Santos (Confins)
The approach to different thematic areas in the context of territorial planning and management requires not only the synergy of actions but also the availability of access to organized and standardized data through databases, thus constituting an essential tool for the promotion and effective response to demands. In this regard, this article aims to present the guidelines adopted by the Water Security Panel for the construction of a geospatial database dedicated to water resources management and applied to territorial intelligence. A methodology based on the National Spatial Data Infrastructure was adopted, involving the consultation of 15 official open databases and conducting assessments of completeness, logical consistency, positional accuracy, temporal accuracy, and thematic accuracy. Consequently, an integrated database was developed, comprising 410 vector layers organized into eight thematic categories: water resources, sanitation, infrastructure, basic cartography and territorial boundaries, disasters, land use and cover, irrigation, and demography.